(Aza)pentacenes clipped into a ring: stabilization of large (aza)acenes - Ahrens, Lukas; Tverskoy, Olena; Weigold, Svenja; Ganschow, Michael; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2021)
A doubly alkylene bridged 6,13-diphenylpentacene and analogously bridged azapentacenes were prepared; they are persistent. The doubly bridged azapentacenes display superior photochemical, oxidative and thermal stabilities compared to azapentacenes protected by bis(TIPS-ethynyl)-substituents—clipping an azaacene into a large ring is a viable complement in stabilization.